2022
DOI: 10.3390/ijerph19041941
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors Associated with Adolescents’ and Young Adults’ Susceptibility, Use, and Intended Future Use of Different E-Cigarette Devices

Abstract: Numerous studies have identified sociodemographic factors associated with susceptibility, ever-use and past-30-day use of e-cigarettes, including JUUL. However, it remains unknown which sociodemographic factors are associated with adolescents’ and young adults’ (AYA) use of the entire spectrum of different types of e-cigarette devices (e.g., disposables, pod/cartridge-based, and other e-cigarettes, like mods or tanks). The aim of this study was to examine the relationship between sociodemographic factors and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This study provides some evidence to inform regulations of ENDS device and liquid characteristics and interventions for people with specific attributes. We found that, in 2023, the group of women who are younger and LGBTQ + was more likely to use non-adjustable disposable devices with a nicotine salt liquid such as Elf Bar, however, a study in 2020 found that people aged 13-24who identified as LGBTQ + were more likely to use disposable pods ( Gaiha et al, 2022 ). The inconsistent findings may be attributed to the rapidly changing ENDS market.…”
Section: Discussionmentioning
confidence: 88%
“…This study provides some evidence to inform regulations of ENDS device and liquid characteristics and interventions for people with specific attributes. We found that, in 2023, the group of women who are younger and LGBTQ + was more likely to use non-adjustable disposable devices with a nicotine salt liquid such as Elf Bar, however, a study in 2020 found that people aged 13-24who identified as LGBTQ + were more likely to use disposable pods ( Gaiha et al, 2022 ). The inconsistent findings may be attributed to the rapidly changing ENDS market.…”
Section: Discussionmentioning
confidence: 88%
“…As only tweets in English were included, it is likely that people of White ethnic origin were overrepresented for tweets in both countries. Indeed, previous studies have reported complex, and sometimes subtle, differences in ENDS perceptions, intentions and use among people of different ethnicities [50] , [51] . Though we explored the relative presence of bot-like users among tweet topics, we did not exclude bots meaning the topics derived may not wholly represent those discussed by genuine Twitter users.…”
Section: Discussionmentioning
confidence: 99%
“…Further research can examine additional individual and social factors associated with susceptibility to future vaping among Latino adolescents to inform future prevention and intervention actions. Such factors could include intention to use e-cigarettes, normative beliefs, social acceptability, friendship network exposure, and low socioeconomic status, which have previously been identified as significant predictors of e-cigarette use initiation and susceptibility to future vaping [38,40,41].…”
Section: Discussionmentioning
confidence: 99%